The Role of Kampung Teluk Kepayang as Cultural Heritage in Elevating Malay Culture - Ibrahim, Nur Syaidatul Athirah; Kasim, Mohamad Rozi (Melayu: Jurnal Antarabangsa Dunia Melayu, 2024)
In an effort to deepen the culture of the Malay people, the continuation of heritage and culture by the next generation can lift and preserve Malay cultural traditions in the community, especially in the younger generation. The preservation of Malay culture in society needs to be strengthened to prevent it from being marginalized and under threat. The cultural heritage village, Kampung Teluk Ketapang in Bota Kiri, Perak, has its own uniqueness and is different from other villages in Malaysia, where this village was formed as an initiative to dignify the cultural heritage of the Perak community. Therefore, the objective of this study is to examine the role of this village in uplifting Malay culture. This study has used the program proposed by the Cultural Mapping of the National Department of Culture and Arts (JKKN) for the sub-culture section and analysed the data on the cultural activities. The results of the study found that the cultural and traditional activities that are still practiced in the said village have helped to revive Malay culture in the community, especially in the current young generation, and to some extent have boosted the tourism industry in Perak. In conclusion, this writing is expected to be able to provide awareness and knowledge to the community about the dignity of Malay culture through the existence of Kampung Teluk Kepayang, Bota Kiri, Perak, and even empower Malay culture in Malaysia. Full text: PDF